Potential Inhibitory and Inducing Effects of Triphala Formulation on Cytochrome P450 Enzymes - Jumpa-Ngern, Piracha; Plengsuriyakarn, Tullayakorn; Mahavorasirikul, Wiratchanee; Na-Bangchang, Kesara (Trends in Sciences, 2022)
Triphala formulation is one of the most common traditional medicines used for several health conditions. The study aimed to investigate the inhibitory and inducing potentials of Triphala formulation, including its active compounds gallic acid and ellagic acid, on cytochrome P450 (CYP450) enzymes. The inhibitory effects of Triphala formulation, gallic acid and ellagic acid on the 5 major human CYP450 enzymes were evaluated using a bioluminescent CYP450 inhibition assay. Evaluation of inducing effect of Triphala formulation on CYP1A2 and CYP3A1 mRNA expression following daily oral doses of 1,000 and 5,000 mg/kg body weight for 28 days was evaluated using RT-PCR. Gallic acid potently inhibited CYP1A2, CYP2C9 and CYP2C19 with a non-competitive nature, while the inhibitory potencies on CYP2D6 and CYP3A4 were weak. Chronic dosing of Triphala formulation at 1,000 and 3,000 mg/kg body weight significantly induced mRNA expression of CYP1A2 but not CYP3A1. Results suggest the propensity of metabolic drug interactions when Triphala formulation was concurrently administered with other conventional drugs or herbal medicines. HIGHLIGHTS Gallic acid potently inhibited CYP1A2, CYP2C9 and CYP2C19 with a non-competitive nature Triphala formulation at the dose of 1,000 and 3,000 mg/kg body weight significantly induced mRNA expression of CYP1A2 Results suggest the propensity of metabolic drug interactions when Triphala formulation is concurrently administered with conventional drugs or herbal products by human CYP450 enzymes, particularly CYP1A2, CYP2C9 and CYP2C19 GRAPHICAL ABSTRACT